Tradition of Pacu Jalur in Kuantan Singingi - Sri Chairani; Ria Asmeri Jafra; Dian Meliza (Lakhomi Journal Scientific Journal of Culture, 2022)
Kuantan Singingi is one of the regencies in Riau province. It is rich in cultural arts, languages, customs, traditions, etc. One of them is the tradition of pacu jalur in Kuantan Singingi (a.k.a Rantau Kuantan). This tradition has existed for a long time and it is still exist until now due to the community of Kuantan Singingi still preserve it. As the result, the tradition of pacu jalur has a very high cultural values. Pacu jalur is a rowing regatta with traditional long boat typical of Kuantan Singingi (Kuansing). It held every year to celebrate the Independence day of Republic Indonesia and also includes traditional ceremonies typical of Kuansing. Pacu Jalur festival is a traditional festival emerged from a rich history of Kuantan Singingi and has survived various iterations for more than a century. The purpose of this study is to describe the tradition of Pacu Jalur in Kuantan Singingi, from the history of Pacu Jalur to the celebration of Pacu Jalur Festival, so that the outside community will know more about this tradition. Descriptive qualitative methods were used in this study. Observation, interview, and documentation were used to collect data. From this study, it can be concluded that there is a need to study revitalization of pacu jalur with the result whole processes, activities and arts related to pacu jalur activities are documented and are copyrighted as the tradition of Kuantan Singingi community, because this tradition is the great pride for them.